Removal of patient-specific reconstruction plates after mandible reconstruction with a fibula free flap: is the plate the problem?. Issue 2 (February 2022) - Kreutzer, K.; Steffen, C.; Nahles, S.; Koerdt, S.; Heiland, M.; Rendenbach, C.; Beck-Broichsitter, B.
Abstract: Computer-aided microvascular mandible reconstruction is an increasingly common procedure in oral and maxillofacial surgery. The aim of this retrospective single-centre study was to evaluate the rate and specifics of hardware removal after fibula free flap (FFF) fixation with a patient-specific reconstruction plate. The study included patients who underwent hardware removal between April 2017 and October 2019. Statistical analyses were performed regarding the different indications for plate removal (dental implantation versus complication) and the surgical approach (intraoral versus extraoral). Plate removal was performed in 29 of 98 patients (29.6%) after FFF fixation with a patient-specific reconstruction plate. Plate removal was done prior to dental implantation in 58.6% of cases and due to complications in 41.4%. Complications seen between reconstructive surgery and plate removal were less frequent in the dental rehabilitation group (8/17 vs 12/12; P  = 0.002). Within this group, 35.3% of plates were removed intraorally, and the majority of partial plate removals were performed in the patients with plate removal for dental rehabilitation (72.7% vs 27.3%). Hospitalization was shorter with an intraoral approach (1.7 days vs 4.0 days, P  = 0.052). The removal of patient-specific reconstruction plates prior to dental implantation is often partial and can be performed intraorally. The use of patient-specific miniplates for fixation of FFF might facilitate later dental rehabilitation.